2006
DOI: 10.1111/j.1349-7006.2006.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss or down‐regulation of HLA class I expression at the allelic level in freshly isolated leukemic blasts

Abstract: Loss or down-regulation of human leukocyte antigen (HLA) class I expression has been demonstrated in a variety of solid tumors. To date, such altered HLA expression has not been studied extensively in freshly isolated leukemic blasts. If it occurs, leukemic cells could escape T-cell surveillance as a consequence. Genotypes of nine leukemic cell lines were determined using a polymerase chain reaction for HLA classes I and II. Cells were also examined for HLA β β β β2-microglobulin, and allele-specific HLA prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 42 publications
1
55
0
1
Order By: Relevance
“…The pool of the CCRF-CEM HSPA eluted peptides shown in Table 1 was subjected to HLA class I epitope database searches with the restrictions to the HLA alleles of the cell line. The leukemic cell line, CCRF-CEM, has been reported to express HLA class I alleles, including A*0101, 31012; B*0801, 4001 and C*0304, 0701 (Adams et al 2005;Masuda et al 2007). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The pool of the CCRF-CEM HSPA eluted peptides shown in Table 1 was subjected to HLA class I epitope database searches with the restrictions to the HLA alleles of the cell line. The leukemic cell line, CCRF-CEM, has been reported to express HLA class I alleles, including A*0101, 31012; B*0801, 4001 and C*0304, 0701 (Adams et al 2005;Masuda et al 2007). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although some studies suggested that the expression of HLA class I is low in myeloid malignancies (49), this was relative to the much higher levels on lymphoid cells (autologous T cells). In fact, other studies reported relatively intact levels of HLA class I in acute leukemia (50,51). Experimentally, NK cells expanding in response to CMV have a heightened cytolytic potential, but only against mismatched blasts, because they are efficiently inhibited by cognate HLA class I molecules (L.L.…”
Section: Discussionmentioning
confidence: 99%
“…Most types of solid tumors display defects in HLA class I expression, but the incidence of HLA class I downregulation and complete HLA class I allele loss varies among different types of tumors. 15 In contrast to solid tumors, HLA class I expression in leukemia has not been extensively studied, except in acute leukemia [16][17][18][19][20] and B-CLL. 21 In most of these studies, complete loss of HLA class I allele(s) in leukemic cells was infrequent.…”
Section: Cell Surface Expression Of Hla Class I Moleculesmentioning
confidence: 99%